The Impact Of Online Learning For Teachers In Remote Areas - Tuminah Tuminah; Yustina Selong; Kunto Nur Cahyoko (STKIP Singkawang, 2022)
Online learning in remote areas is certainly not as easy as online learning in big cities in Indonesia. Online learning in remote areas, especially in the Landak district, faces many obstacles due to limited facilities and infrastructure. To overcome these problems, teachers in remote areas in Landak are trying to find solutions so that online learning can still take place well, even though it is limited. This study aims to describe the difficulties experienced by teachers when teaching and the solutions offered to overcome the problems of online learning in these remote areas. The results of this study indicate that there are still some difficulties encountered related to online learning experienced by teachers in remote areas. Difficulties in the internet network and the provision of laptops or smartphones still color the implementation of online learning experienced by teachers in remote areas. 84% of teachers experienced network difficulties in the online learning process during the pandemic. One thing is very proud that teachers in remote areas are willing to do anything to overcome these difficulties. So even though there are many difficulties faced by online learning in remote areas, it can still run well. One of the efforts made is blended learning, taking turns online and offline learning.